2020
DOI: 10.26815/acn.2020.00108
|View full text |Cite
|
Sign up to set email alerts
|

Deep Phenotyping in 1p36 Deletion Syndrome

Abstract: Although 1p36 deletion syndrome is the most common terminal deletion syndrome, unexplained phenotypic variability still occurs. We aimed to delineate the phenotype of this syndrome in detail and to characterize the phenotype-genotype correlation. Methods: We retrospectively reviewed 15 patients diagnosed with 1p36 deletion syndrome confirmed by chromosomal microarray. Results: All 15 patients revealed delayed attainment of motor milestones and speech. Seven patients (46.7%) never walked alone and only two (13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Additionally, they found expressive language to be absent in about 75% of patients, limited to a few isolated words in 17%, and at the level of two word phrases in 8% [3]. Similarly, poor expressive language has been reported by other studies [9,10]. Overall, speech/language development seems to be significantly more impaired than motor development [9].…”
Section: Introductionmentioning
confidence: 53%
“…Additionally, they found expressive language to be absent in about 75% of patients, limited to a few isolated words in 17%, and at the level of two word phrases in 8% [3]. Similarly, poor expressive language has been reported by other studies [9,10]. Overall, speech/language development seems to be significantly more impaired than motor development [9].…”
Section: Introductionmentioning
confidence: 53%
“…Craniofacial malformation is a prominent phenotype in those with the 1p36 deletion. 18 The 15q duplication was the most common duplication in our IESS cohort. In a study of 83 patients with 15q duplication, 63% were reported to have epilepsy, 42% of whom diagnosed with infantile spasms.…”
Section: Cnvsmentioning
confidence: 84%
“…In our study, 6 patients with IESS also had other seizure types, including focal seizures, tonic seizures, and myoclonic seizures. Craniofacial malformation is a prominent phenotype in those with the 1p36 deletion 18 . Bahi‐Buisson et al reported 53 epilepsy patients with 1p36 deletion, and about one‐third of the patients (19/53) developed refractory epilepsy 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Deep phenotyping, or "the precise and comprehensive analysis of phenotypic abnormalities in which the individual components of the phenotype are observed and described" 7 , is a fundamental component of precision medicine that requires timely synthesis of multiple types of patient data 19,20 . Deep phenotyping has been successfully applied to rare disease and genetic disorders [21][22][23][24][25][26][27][28][29][30][31][32][33] , cancer [34][35][36][37][38][39][40] , and pregnancy [41][42][43] using a variety of clinical and -omic data. Despite large-scale biobanking efforts and resources like the UK Biobank (https://www.ukbiobank.ac.uk) and the All of Us (AoU) Research Program (https://www.researchallofus.org), most EHRs do not systematically integrate nor have the infrastructure to integrate patient-level genomic data or other forms of external knowledge (e.g., scientific literature) with clinical data [44][45][46] .…”
Section: Introductionmentioning
confidence: 99%